Fish supply and demand for food security in Sub-Saharan Africa: An analysis of the Zambian fish sector - Tran, Nhuong; Chu, Long; Chan, Chin Yee; Genschick, Sven; Phillips, Michael; Kefi, Alexander Shula (Elsevier, 2019)
The demand for fish in Sub-Saharan Africa, as driven by the trend of diet-shift to fish, economic and demographic growth, outstrips supply. The resulting fish deficit is drawing attention of policy makers as it poses threats to economic stability as well as food security in the region. In this paper, a multi-species, multi-sector equilibrium model is developed and applied to Zambia as a case study to provide a tool for policy makers to examine the interaction between fish supply and demand. Projection results show that under business-as-usual scenario, the fish deficit in Zambia will increase and fish import will be a key contributor of fish for consumption in 2030. Increasing import tax will not solve the fish deficit due to a limited substitution between domestic and imported fish, while this tariff restriction may increase the fish price and affect poor people. The model results suggest that further investment in aquaculture could provide a solution if input markets for seed and feed are appropriately developed. Though calibrated to Zambia's fish sector, the model can be applied to analyze the outlook of fish sectors in other developing countries.